Superficial Parotidectomy by Retrograde Facial Nerve Dissection - Gurung, Narendra Vikram; Shrestha, D; Acharya, A; Gurung, A; Shrestha, S; Poudel, SR; Chapagain, A; Regmi, SM (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: Tumors of the salivary gland are relatively uncommon and represent less than two percentage of all head and neck neoplasms. Parotid gland tumor comprises 85% of the salivary gland tumors of which 80% are being benign. Superficial parotidectomy is the commonest procedure done for parotid tumors which can be performed by either anteretrograde or retrograde facial nerve dissection technique.Methods: Outcome of 60 patients after superficial parotidectomy with retrograde facial nerve dissection has been studied.Results: Total of 60 patients had been studied. Complications like facial nerve weakness, Freys syndrome, salivary fistula, and wound infection were taken into account. Among them, 13.33% patients developed temporary facial nerve weakness, followed by temporary salivary fistula, 1.6%. None of the patients developed any severe complication.Conclusion: Superficial parotidectomy by retrograde facial nerve dissection is an easy technique to carry out with low complication rate and without compromising surgical outcome.Journal of Gandaki Medical CollegeVol. 10, No. 1, 2017, page: 25-27